2019
DOI: 10.1017/s003118201900060x
|View full text |Cite
|
Sign up to set email alerts
|

Association and predatory capacity of fungi Pochonia chlamydosporia and Arthrobotrys cladodes in the biological control of parasitic helminths of bovines

Abstract: Nematophagous fungi are used in the biological control of the parasitic helminths of animals and plants. The association of ovicidal and predator nematophagous fungi may present a complementary and increased action on the biological control of helminths. Joint growth compatibility and predation tests were carried out on infective larvae of nematode parasites of bovines with the nematophagous fungus ovicide Pochonia chlamydosporia and the nematophagous fungus predator Arthrobotrys cladodes. The tests of antagon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…The fungus Pochonia chlamydosporia predates nematode eggs through appressory structures, which promote mechanical and enzymatic action of egg penetration (Braga et al ., 2008) and has larvicidal action on gastrointestinal parasitic nematodes of cattle (Vieira et al ., 2019). The fungus Arthrobotrys cladodes produces traps that promote the adhesion, immobilization, penetration and destruction of nematode larvae (Oliveira et al ., 2018 a ).…”
Section: Introductionmentioning
confidence: 99%
“…The fungus Pochonia chlamydosporia predates nematode eggs through appressory structures, which promote mechanical and enzymatic action of egg penetration (Braga et al ., 2008) and has larvicidal action on gastrointestinal parasitic nematodes of cattle (Vieira et al ., 2019). The fungus Arthrobotrys cladodes produces traps that promote the adhesion, immobilization, penetration and destruction of nematode larvae (Oliveira et al ., 2018 a ).…”
Section: Introductionmentioning
confidence: 99%
“…Vieira et al . (2019) reported that the combined use of the fungi A. cladodes and P. chlamydosporia obtained, under laboratory conditions, higher nematicidal activity over bovine parasitic nematodes than A. cladodes and P. chlamydosporia used separately. It is necessary to carry out studies under natural conditions to evaluate the effect of combined use of nematophagous fungi on the biological control of bovine parasitic nematodes, since the temperature and nutrient availability conditions of the environment vary during the year and do not meet the needs growth of all fungal strains.…”
Section: Discussionmentioning
confidence: 99%
“…Arthrobotrys cladodes and D. flagrans produce traps that promote adhesion, immobilization, penetration and destruction of nematode larvae (Grønvold et al, 1996;Oliveira et al, 2018a). Pochonia chlamydosporia parasites eggs of nematodes through structures known as apressories, which promote egg penetration by mechanical and enzymatic action (Zare et al, 2001;Stroze et al, 2013) and presents larvicidal action on bovine parasitic nematodes (Vieira et al, 2019). According to Mukhtar & Pervaz (2003), Van Ooij (2011) and Yang et al (2013), enzymes and toxins produced by P. chlamydosporia are capable of killing of nematode larvae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fungi are selected based on their chitin degrading and antiparasitic properties reported in literature [ 17 , 18 , 19 ]. P. chlamydosporia , whose ovicidal activity on nematode eggs is already known [ 20 , 21 ], is chosen as a model to be compared against the inhibiting activity of the other selected fungi.…”
Section: Introductionmentioning
confidence: 99%